The Effect of Discipline, Working Environment and Motivation on Employee Performance: The Case of Regional Secretariat Office at Ogan Komering Ulu Regency - Khairunnisa, Putri; Idris, Muhammad; Nurrahmi, Maftuhah (International Journal of Marketing & Human Resource Research, 2025)
This research aims to determine 1) The influence of work discipline, work environment, and motivation on employee performance at the Ogan Ilir Regency Secretariat, 2) The influence of work discipline on employee performance at the Ogan Ilir Regency Secretariat, 3) The influence of work environment on employee performance at the Ogan Ilir Regency Secretariat 4) The influence of motivation on employee performance at the Ogan Ilir Regency Secretariat. The type of research in this study is associative, utilizing data analysis techniques including multiple linear regression analysis. The sample in this research consisted of 68 employees from the Ogan Ilir Regency Secretariat, who were selected using a purposive sampling technique. The data used in this research were primary data collected using a questionnaire data collection method. The results of this research indicate that 1) Work discipline, work environment, and motivation have a positive and significant effect on employee performance. 2) Work discipline has a positive and significant effect on employee performance. 3) Work environment has a positive and significant effect on employee performance. 4) Motivation has a positive and significant effect on employee performance.